Lung Mechanics Over the Century: From Bench to Bedside and Back to Bench - Biselli, Paolo Jose Cesare; Degobbi Tenorio Quirino Dos Santos Lopes, Fernanda; Righetti, Renato Fraga; Moriya, Henrique Takachi; Tibério, Iolanda Fátima Lopes Calvo; Martins, Milton Arruda (Frontiers in Physiology, 2022)
Lung physiology research advanced significantly over the last 100 years. Respiratory mechanics applied to animal models of lung disease extended the knowledge of the workings of respiratory system. In human research, a better understanding of respiratory mechanics has contributed to development of mechanical ventilators. In this review, we explore the use of respiratory mechanics in basic science to investigate asthma and chronic obstructive pulmonary disease (COPD). We also discuss the use of lung mechanics in clinical care and its role on the development of modern mechanical ventilators. Additionally, we analyse some bench-developed technologies that are not in widespread use in the present but can become part of the clinical arsenal in the future. Finally, we explore some of the difficult questions that intensive care doctors still face when managing respiratory failure. Bringing back these questions to bench can help to solve them. Interaction between basic and translational science and human subject investigation can be very rewarding, as in the conceptualization of ´Lung Protective Ventilation´ principles. We expect this interaction to expand further generating new treatments and managing strategies for patients with respiratory disease.